Asuhan Keperawatan Medikal Bedah Pada Pasien Dengan Chonic Kidney Disease (CKD) Stage V Di Ruang Interne, Di Rsud Prof. H.Muhammad Yamin, S.H Pariaman - Adyenda Ratu Hidayah; Debby Silvia Dewi; Linda Marni; Hilma Yessi (Jurnal Ilmu Psikologi dan Kesehatan | E-ISSN : 3063-1467, 2026)
Chronic Kidney Disease (CKD) is a global health problem with an increase in the burden of disease of around 29%–41% in the last three decades. The prevalence of CKD in all stages (1–5) reached 13.4%, while advanced stages (3–5) were around 10.6%. Globally, around 788 million people live with CKD (±14.2%) and it is the 9th leading cause of death in the world (WHO, 2023; ISN, 2023). In Indonesia, the prevalence of CKD was 3.8% (Riskesdas), while in West Sumatra it was around 0.2%. Prof. H. Muhammad Yamin Regional General Hospital in 2025 recorded 335 cases of CKD with 16 deaths in CKD Stage V, indicating that CKD is still a serious problem, especially in advanced stages with complications of hypervolemia due to decreased kidney function. This study aims to describe medical-surgical nursing care for patients with CKD Stage V during 4 days of treatment. The method used was a descriptive case study on Mrs. S in the Internal Room of Prof. H. Muhammad Yamin Regional Hospital through interviews, observations, physical examinations, and documentation. The results established seven nursing diagnoses, namely, ineffective breathing patterns, hypervolemia, ineffective peripheral perfusion, activity intolerance, nausea, acute pain, and the risk of impaired skin/tissue integrity. Interventions focused on fluid management, respiratory optimization, activity intolerance, pain management, and prevention of impaired skin integrity. Evaluation showed temporary improvement in nausea and pain., ineffective breathing patterns, ineffective peripheral perfusion, and activity intolerance improved for a while, but decreased on the fourth day. The risk of impaired skin integrity was not found until the end of treatment, but the patient's condition worsened until he died on the fourth day due to the progression of terminal illness. The conclusion emphasized the need for close, comprehensive, and continuous monitoring in Stage V CKD patients and improvement of nursing service facilities.